Semiotic Analysis in the Film Barbie (2023): Representation of Patriarchal Culture - Della Setya Anggraini; Sugeng Harianto; Refti Handini Listyani (International Journal of Social Sciences and Humanities, 2026)
The research aims to meticulously explore and analyze the manifestation of patriarchal culture depicted in the film "Barbie Live Action 2023". It employs a qualitative approach, focusing on scenes that vividly and deeply illustrate how patriarchal norms reflect within the presented gender context. Through meticulous data analysis, the identification of symbols, dialogues, and character interactions becomes the spotlight, highlighting and illustrating the reinforcement of strong patriarchal gender norms portrayed in the film. The study yields a profound understanding of how the film reinforces and portrays gender stereotypes both visually and narratively, unmistakably showcasing the conflict between two worlds, each reinforcing established gender paradigms.Within the framework of liberal feminism theory, this analysis provides clear insights into the construction of gender in visual media and the urgency for a shift in evolving gender perspectives within society. From the perspective of gender equality, "Barbie Live Action" serves not only as a complex elucidation of patriarchal culture but also as a call for a change in gender perspectives within society. The semiotic analysis and application of liberal feminist theory in this study offer profound insights into the messages of gender equality conveyed by the film and its broader impact on gender awareness within society.